Helicobacter pylori induced miR-362-5p upregulation drives gastric cancer progression and links hepatocellular carcinoma through an exosome-dependent pathway - Zhang, Jianhui; Liu, Shuzhen; Zhang, Juan; Feng, Mingzhu; Chen, Shu; Zhang, Yinuo; Sun, Zekun; Cao, Xinying; Gao, Chao; Ji, Xiaofei; Zhao, Huilin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHelicobacter pylori (H. pylori) infection induced miRNA dysregulation plays an important role in gastric cancer (GC) and exosomes mediate the spread of pathogenic effects.MethodsExpression of miR-362-5p and its clinical significance in GC were analyzed using data from TCGA. The effects of miR-362-5p on GC cells’ proliferation and migration were examined by using CCK-8, EdU, transwell and scratch assays. MKN45 xenograft model in nude mice was employed to evaluate impacts of miR-362-5p on GC progression in vivo. Target gene of miR-362-5p was screened by bioinformatic analysis and verified by using dual-luciferase assay. Exosomes from H. pylori-infected GES-1 cell (Hp-GES-EVs) were isolated and miR-362-5p inside the exosome was detected. The uptake of exosome by GC cells was observed through fluorescence imaging and exosome-mediated pathogenesis was explored. Furthermore, the transport of exosome-mediated miR-362-5p via blood was examined. The effect of exosome-carried miR-362-5p on hepatocellular carcinoma (HCC) progression was investigated by hepatocyte’s uptake, proliferation and migration assays.ResultsmiR-362-5p was significantly upregulated in GC tissues associated with H. pylori infection. Downregulation of miR-362-5p in GC cells inhibited proliferation and migration in vitro and suppressed tumor growth in vivo, counteracting H. pylori-induced carcinogenesis. TLE4 was confirmed as a direct target of miR-362-5p, and miR-362-5p/TLE4 axis implicated in H. pylori-driven neoplastic transformations in GC cells. Hp-GES-EVs mediated the transport of miR-362-5p, was absorbed by GC cells and detected at elevated levels in the serum of infected mice. Moreover, Hp-GES-EVs were diffused to liver and taken up by liver cells, enhancing HCC cell proliferation and migration by targeting TLE4.ConclusionH. pylori infection upregulates miR-362-5p, facilitating GC progression via TLE4 targeting. Exosome-mediated transfer amplifies its effects, contributing to liver damage and potentially facilitating HCC.